Trace Elements Measurement of Mangium Wood (Acacia mangium) by AAS - Nyoman J Wistara; Evelin Yustiana (Masyarakat Peneliti Kayu Indonesia, 2014)
The ash and metals content of Acacia mangium Wild was determined following standard procedures of TAPPI T211 om-93 test method and wet ashing procedures with HNO3 and HClO4 solution, respectively. Measurements of trace elements were carried out by the use of atomic absorption spectrometry (AAS). Although it was fluctuating, the lowest ash content was found in a 5 years old wood and then tended to increase in older three. In the 3 and 5 years old wood, the ash content decreased from upper end to the lower end of the stems. In the 7 and 9 years old wood, the lowest ash content was in the middle part and it tends to increase to the lower end of the stem. Ash content of sapwood was higher than that of heartwood. The content of Mg decreased with increasing age of wood, and other metals tended to increase with the increase of wood age. Metallic components of acacia wood tended to accumulate more in sapwood compared to these in heartwoods. Vertically, the content of Mg and Cu decreased from upper end to lower end of the stems, and in contrary to these of other metals.Key words: atomic absorption spectrometry, Acacia mangium, closed loop cycle, metallic contents, oxygen-based bleaching